Is preoperative CT-guided biopsy a valuable tool in the diagnostic workup of patients with visceral and retroperitoneal sarcoma?. Issue 155 (October 2022) - Luca Alatzides, Georgios; Luisa Steinberg, Hannah; Schildhaus, Hans-Ulrich; Hamacher, Rainer; Kaths, Moritz; Grueneisen, Johannes; Treckmann, Jürgen; Bauer, Sebastian; Umutlu, Lale; Schaarschmidt, Benedikt
Abstract: Purpose: We aimed to analyze the diagnostic accuracy of preoperative CT-guided biopsy to identify patients that might profit from neoadjuvant chemotherapy in a specialized high-volume sarcoma center. Material and Methods: We retrospectively reviewed all patients with suspected soft tissue tumors of the abdomen cavity including the retroperitoneum, who received CT-guided biopsy followed by surgical tumor resection. Sensitivity, specificity, PPV and NPV were calculated in all patients with abdominal sarcomas at our hospital. A subgroup analysis was performed for patients with liposarcoma. Results: A total of 82 patients (35 female, 47 male, age: 62.0 ± 14.7) received preoperative CT-guided biopsy followed by surgical resection. Overall accordance of CT-guided biopsy to identify final histology was 77 %. CT-guided biopsy revealed the diagnosis of liposarcoma in 23 patients whereas final analysis of the surgical specimen identified liposarcoma in 29 patients. Here, sensitivity, specificity, PPV and NPV was 79.3 %, 100.0 %, 100.0 % and 89.8 % respectively. Subgroup analysis revealed a better accuracy for correctly identifying patients with well-differentiated liposarcoma than patients with dedifferentiated liposarcoma (75.0 % vs 62.5 %). In patients with other sarcoma, sensitivity, specificity, PPV, NPV and diagnostic accuracy was 87.5 %, 95.5 %, 82.4 % and 96.9 %, respectively. Conclusion: CT-guided biopsy in a specialized high-volume sarcoma center is an accurate and effective method to assess patients with abdominal sarcoma and especially abdominal liposarcoma. Therefore, it is an indispensable tool in the pretherapeutic workup process. Nevertheless, our study underlines the previously reported difficulties in dedifferentiated liposarcoma diagnostics, whereby these patient cohort would profit the most from a neoadjuvant therapy regime.